Correction: Bandgap-adjustment and enhanced surface photovoltage in Y-substituted LaTaIVO2N. Issue 26 (24th June 2020) - Bubeck, Cora; Widenmeyer, Marc; De Denko, Alexandra T.; Richter, Gunther; Coduri, Mauro; Salas Colera, Eduardo; Goering, Eberhard; Zhang, Hongbin; Yoon, Songhak; Osterloh, Frank E.; Weidenkaff, Anke
Abstract : Correction for 'Bandgap-adjustment and enhanced surface photovoltage in Y-substituted LaTa IV O2 N' by Cora Bubeck et al., J. Mater. Chem. A, 2020, 8, 11837–11848, DOI: ; 10.1039/D0TA02136A .